Purity Analysis of Gases Used in the Preparation of Reference Gas Standards Using a Versatile OPO-Based CRDS Spectrometer - Stefan Persijn (Journal of Spectroscopy)
Preparation of accurate reference gas standards at low amount fractions such as for greenhouse gases requires highly sensitive instrumentation to determine the purity of the gases used in the preparation. For this purpose, a versatile CRDS spectrometer has been constructed at VSL based on high-power, continuous wave OPOs covering a very wide wavelength range of 2.3–5.1 µm. Due to the use of passivated materials, the spectrometer is also suitable for the measurement of reactive impurities. Details of the spectrometer are presented together with several examples of purity analysis.